ENSURING INCREASED DURABILITY OF PAVEMENT ON REINFORCED CONCRETE ROAD BRIDGES - Mirchuk Iryna Olehivna; Onyshchenko Artur Mykolayovych (World Science, 2024)
The article contains the results of a study on increasing the durability of pavement on reinforced concrete road bridges by using rubber crumb. The pavement on reinforced concrete road bridges is one of the main structural elements of the structure, the technical condition of which affects the safety of the structures as a whole. Given the constant increase in traffic intensity and load on the road network, as well as insufficient funding for major repairs or reconstruction, it is necessary to use materials that ensure reliable operation of the roadway of bridge structures to increase the durability of the asphalt pavement. The asphalt concrete pavement of a roadway has a number of important factors that ensure the safety and comfort of vehicular traffic, namely: flatness, low noise and roughness, which provides the necessary grafting coefficient with the car tires while driving. However, it should be noted that during operation, such a coating is easily exposed to unfavorable factors, which leads to premature deformation in it.